2018
DOI: 10.1007/s12035-018-1149-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid from Patients with Sporadic Amyotrophic Lateral Sclerosis Induces Degeneration of Motor Neurons Derived from Human Embryonic Stem Cells

Abstract: Disease modeling has become challenging in the context of amyotrophic lateral sclerosis (ALS), as obtaining viable spinal motor neurons from postmortem patient tissue is an unlikely possibility. Limitations in the animal models due to their phylogenetic distance from human species hamper the success of translating possible findings into therapeutic options. Accordingly, there is a need for developing humanized models as a lead towards identifying successful therapeutic possibilities. In this study, human embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 108 publications
1
9
0
Order By: Relevance
“…Seven of these studies were quantitative in nature and observed significant increases in the levels of different apoptotic markers, including caspase-3 and caspase-9, following exposure to ALS–CSF compared to controls. However, the increase in Bcl-2 levels following ALS–CSF exposure did not reach statistical significance ( Ding et al , 2015 ; Sumitha et al , 2019 ). The remaining study, which only qualitatively evaluated apoptosis, reported the presence of TUNEL-stained nuclei in cells exposed to ALS–CSF, but not in those from control groups ( Vijayalakshmi et al , 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of these studies were quantitative in nature and observed significant increases in the levels of different apoptotic markers, including caspase-3 and caspase-9, following exposure to ALS–CSF compared to controls. However, the increase in Bcl-2 levels following ALS–CSF exposure did not reach statistical significance ( Ding et al , 2015 ; Sumitha et al , 2019 ). The remaining study, which only qualitatively evaluated apoptosis, reported the presence of TUNEL-stained nuclei in cells exposed to ALS–CSF, but not in those from control groups ( Vijayalakshmi et al , 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro culture models included spinal cord cultures, cortical neuron cultures and motor neuron cultures, as well as cell lines, such as NSC-34 (mouse spinal cord-neuroblastoma hybrid cell line), VSC 4.1 (cholinergic cAMP-differentiated motor neuron-neuroblastoma hybrid cell line) and U251 (human glioma cell line). One recent study also assessed cytotoxicity in motor neurons differentiated from human embryonic stem cells ( Sumitha et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of GSK‐3ß cascade is known to be functionally associated with pro‐inflammatory changes and microglial activation, which is a well‐established marker of ALS histopathology, and the FUS‐ALS forms in particular . GSK‐3ß activities are inversely related to neurotrophin expression, and its downregulation is another recognized molecular feature of human ALS . GSK‐3ß is also implicated in the mechanisms of microglial activation during neurodegeneration .…”
Section: Discussionmentioning
confidence: 99%
“…Although CSF from ALS patients is now known to be constitutionally abnormal [ 18 , 27 ], with raised levels of proteins, including TDP-43 and neurofilaments [ 115 , 210 ], its toxicity started being recognised early on, when it was shown to significantly reduce the survival of rat primary neuronal cultures [ 45 ]. Since then, numerous studies have been performed on various cell types, including NSC-34 cell lines, and, more recently, hESC-derived and iPSC-derived motor neurons, showing greater degeneration when the cells were exposed to CSF from ALS patients than to CSF from control patients [ 33 , 136 , 189 , 197 ]. Interestingly, ALS-CSF was also shown in NSC-34 cells to result in TDP-43 mislocalisation to the cytoplasm, a feature that could be reversed by VEGF [ 174 ].…”
Section: Csf Toxicity In Alsmentioning
confidence: 99%